Innovative technologies in language teaching: critical thinking (Eurasian Journal of Philology Science and Education, 2016)
The Republic of Kazakhstan has changed the paradigm of higher education from teachingin the format «teaching» to the format of «learning» after the signing in 1999 the Bologna Declaration by 29 countries to participate in the process of creating a common educational space. It is no longer a person «teaches» but «learns». In Kazakhstan the main directions of development of functional literacy are listed in the State Program for Education Development of Кazakhstan for 20112020 years. Thus, functional literacy is a social and economic phenomenon related to the welfare of the population and the country as a whole.
Keywords: functional literacy; methods of forming the functional literacy of students; development technology of critical thinking; models of formation and development of functionalliteracy.